Influence of Root Rotation on Delamination Fracture Toughness of Composites - V. Alfred Franklin; T. Christopher; B. Nageswara Rao (International Journal of Aerospace Engineering)
Large deviations have been observed while analysing composite double cantilever beam (DCB) specimens assuming each cracked half as a simple cantilever beam. This paper examines the effect of rotational spring stiffness (K) on the critical fracture energy (GIC) considering nonzero slope at the crack-tip of the DCB specimen by modelling each cracked half as the spring-hinged cantilever beam. The critical load estimates of DCB specimens from GIC are found to be in good agreement with in-house and existing test results of different composite material systems.